On Logarithmic Convexity for Differences of Power Means. (9th January 2008) - Simic, Slavko
Abstract : We proved a new and precise inequality between the differences of power means. As a consequence, an improvement of Jensen's inequality and a converse of Holder's inequality are obtained. Some applications in probability and information theory are also given.